Binderless MDF from Hydroxymethylated Kenaf Pulp - Nyoman J Wistara; Wulan Starini; Fauzi Febrianto; Gustan Pari (Fakultas Kehutanan Universitas Gadjah Mada, 2018)
Modified lignin with improved reactivity can be a potential alternative for synthetic phenol formaldehyde resin for the adhesive of wood composite. Direct hydroxymethylation of kenaf in the present experiments was intended to increase lignin reactivity, and therefore was expected to result in satisfying properties of binderless MDF. The stem of kenaf was refined in a disk refiner and the refined fibers were hydroxymethylated in various levels of alkalinity. The concentration of NaOH during hydroxymethylation was of 3%, 6% and 12%. Wet process was applied to produce MDF (30 cm x 30 cm x 1 cm) with target density of 0.65 g/cm³. Physical and mechanical properties of MDF were measured in accordance with the standard procedure of JIS A 5905: 2003. Chemical changes in the surface of pulp and the change of board crystallinity were evaluated by FTIR-KBr method and X-Ray Diffractometry (XRD), respectively. Density, moisture content, and screw withdrawal of the board increased with increasing of NaOH concentration. Thickness swelling, water absorption, MOE and MOR increased up to 3% concentration of NaOH. The IB and heat conductivity of MDF were not influenced by NaOH concentration. Increasing OH groups due to hydroxymethylation was thought to be the origin of high water absorption and thickness swelling of the resulting boards. Higher alkalinity during hydroxymethylation stage was likely increasing cellulose crystallinity that brought about increasing board density. However, chemical modification of the fiber was thought to be more influential to the bending strength and stiffness of the resulting fiberboard. Hydroxymethylation of kenaf pulp was successfully improved board properties. Except for the moisture content, thickness swelling and internal bonding (at 0% and 3% NaOH concentration), all properties of the MDF satisfied the requirement of JIS A 5905: 2003 (type 5) standard. MDF Tanpa Perekat dari Pulp Kenaf TerhidroksimetilasiIntisariLignin yang telah ditingkatkan reaktifitasnya dapat menjadi bahan alternatif perekat resin sintetis fenol formaldehida. Reaktivitas lignin dapat diperbaiki melalui hidroksimetilasi. Dalam penelitian ini, batang kenaf digiling menggunakan disk refiner, dan selanjutnya dilakukan hidroksimetilasi pada beragam alkalinitas. Konsentrasi NaOH yang digunakan dalam hidroksimetilasi bervariasi dari 3%, 6% dan 12%. Proses basah diterapkan untuk membuat MDF (30 cm x 30 cm x 1 cm) dengan target kerapatan 0,65 g/cm3. Sifat fisis dan mekanis MDF diukur mengikuti prosedur standar JIS A 5905: 2003. Perubahan gugus fungsi permukaan pulp dan tingkat kristalinitas papan masing-masing dievaluasi menggunakan FTIR-metode KBr dan difraksi sinar X (XRD). Hasil penelitian menunjukkan bahwa konsentrasi NaOH tidak mempengaruhi IB dan konduktivitas panas MDF. Kerapatan, kadar air, dan kuat pegang sekrup cenderung meningkat dengan meningkatnya konsentrasi NaOH. Pengembangan tebal, daya serap air, MOE, dan MOR meningkat sampai dengan hidroksimetilasi dalam NaOH konsentrasi 3%. Peningkatan gugus OH serat akibat hidrosimetilasi diduga meningkatkan penyerapan air dan pengembangan tebal papan yang dihasilkan. Alkalinitas hidroksimetilasi yang lebih tinggi meningkatkan gugus cincin aromatik yang menunjukkan bahwa reaksi formaldehida berlangsung dengan lebih baik. Peningkatan alkalinitas dalam hidroksimetilasi meningkatkan kristalinitas selulosa. Peningkatan kristalinitas selulosa diduga berkontribusi dalam meningkatkan kerapatan, namun perubahan gugus kimia serat diduga lebih berpengaruh terhadap MOR dan MOE dari papan serat yang dihasilkan. Hidroksimetilasi pulp kenaf berhasil meningkatkan sifat papan. Kecuali untuk kadar air, pengembangan tebal dan IB (pada hidroksimetilasi dalam 0% dan 3% NaOH), semua sifat-sifat dari MDF yang dihasilkan memenuhi persyaratan standar JIS A 5905: 2003 (tipe 5).